Study of Microalbuminuria and Insulin Resistance in Patients with Essential Hypertension and Metabolic Syndrome and its Relationship to Target Organ Damage - A N Roopa; K S Somashekara Reddy; P Chandrashekara; K R Umabai; H S Madhuvan (Journal of Medical Sciences and Health, 2015)
Aims: To study the prevalence of microalbuminuria, insulin resistance (IR), and metabolic syndrome in patients with essential hypertension (HTN). Materials and Methods: It’s a prospective study done on 50 consecutive hypertensive patients admitted in MVJ Medical College and Research Hospital and compared with controls. Detailed history, clinical examination and anthropometric measurements are taken. Estimation of oral glucose tolerance test, fasting insulin, urine microalbuminuria, fasting lipid profile, serum creatinine, and blood urea are done in all subjects. Standard 12 lead electrocardiogram taken to look for evidence of left ventricular hypertrophy and chest radiograph for cardiomegaly. Fundoscopy was done to look for hypertensive changes. Results: Among the 50 patients studied, microalbiminuria was found in 70% patients. IR (homeostatic model assessment-IR >3.5 μU/ml) was noted in 20% of patients; all these patients had blood pressure (BP) of >190/100 mmHg. Of the total patients, 42.3% were freshly detected and none of them had IR. Dyslipidemia was observed in 61% and obesity in 42% of the patients. About 38.5% patients fulfilled the National Cholesterol Education Program Adult Treatment Panel 3 criteria for metabolic syndrome. Conclusions: In our study 70% of hypertensives had microalbuminuria and correlated directly with degree and duration of HTN, but it was not statistically significant. Patients with dyslipidemia also had (70%) microalbuminuria. Microalbuminuric patients had a higher degree of end organ involvement as compared to normoalbuminuric patients. IR is seen in patients with very high BP and metabolic syndrome.